Contribution of genetic variants to congenital heart defects in both singleton and twin fetuses: a Chinese cohort study - Shaobin Lin; Shanshan Shi; Jian Lu; Zhiming He; Danlun Li; Linhuan Huang; Xuan Huang; Yi Zhou; Yanmin Luo (Molecular Cytogenetics, 2024)
Abstract Background The contribution of genetic variants to congenital heart defects (CHDs) has been investigated in many postnatal cohorts but described in few prenatal fetus cohorts. Overall, specific genetic variants especially copy number variants (CNVs) leading to CHDs are somewhat diverse among different prenatal cohort studies. In this study, a total of 1118 fetuses with confirmed CHDs were recruited from three units over a 5-year period, composing 961 of singleton pregnancies and 157 of twin pregnancies. We performed chromosomal microarray analysis on all cases to detect numerical chromosomal abnormalities (NCAs) and pathogenic/likely pathogenic CNVs (P/LP CNVs) and employed whole-exome sequencing for some cases without NCAs and P/LP CNVs to detect P/LP sequence variants (P/LP SVs). Results Overall, NCAs and P/LP CNVs were identified in 17.6% (197/1118) of cases, with NCA accounting for 9.1% (102/1118) and P/LP CNV for 8.5% (95/1118). Nonisolated CHDs showed a significantly higher frequency of NCA than isolated CHD (27.3% vs. 4.4%, p < 0.001), but there was no significant difference in the frequency of P/LP CNVs between isolated and nonisolated CHD (11.7% vs. 7.7%). A total of 109 P/LP CNVs were identified in 95 fetuses, consisting of 97 (89.0%) de novo, 6 (5.5%) parental inherited and 6 (5.5%) with unavailable parental information. The 16p11.2 proximal BP4-BP5 deletion was detected in 0.9% (10/1118) of all cases, second only to the most common 22q11.21 proximal A-D deletion (2.1%, 23/1118). Most of the 16p11.2 deletions (8/10) detected were de novo, and were enriched in CHD cases compared with a control cohort from a previous study. Additionally, SV was identified in 12.9% (8/62) of cases without NCA and P/LP CNV, most of which were de novo with autosomal dominant inheritance. Conclusions Our cohort study provides a deep profile of the contribution of genetic variants to CHDs in both singleton and twin fetuses; NCA and P/LP CNV contribute to 9.1% and 8.5% of CHD in fetuses, respectively. We confirmed the 16p11.2 deletion as a CHD-associated hotspot CNV, second only to the 22q11.21 deletion in frequency. Most 16p11.2 deletions detected were de novo. Additionally, P/LP SV was identified in 12.9% (8/62) of fetuses without NCA or P/LP CNV.